2018
DOI: 10.1037/cou0000248
|View full text |Cite
|
Sign up to set email alerts
|

Mental Help Seeking Attitudes Scale (MHSAS): Development, reliability, validity, and comparison with the ATSPPH-SF and IASMHS-PO.

Abstract: Attitudes is a key help-seeking construct that influences treatment seeking behavior via intention to seek help, per the theory of planned behavior (TPB). This article presents the development and psychometric evaluation of the Mental Help Seeking Attitudes Scale (MHSAS), designed to measure respondents' overall evaluation (unfavorable vs. favorable) of their seeking help from a mental health professional. In Study 1 (N = 857 United States adults), exploratory factor analysis (EFA), confirmatory factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
130
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(145 citation statements)
references
References 60 publications
9
130
0
6
Order By: Relevance
“…To our best knowledge, the current study was one of the first studies to validate the MHSAS in a different culture and region. The results supported a single factor solution for the Malay MHSAS and the scale's unidimensionality was consistent with the findings of its developers, Hammer et al (16). The present study also provided support for the scale's concurrent validity, and demonstrated high internal consistency of α=.892 [26], a value that is close to the original scale's internal consistency value (α=.92).…”
Section: Discussionsupporting
confidence: 90%
“…To our best knowledge, the current study was one of the first studies to validate the MHSAS in a different culture and region. The results supported a single factor solution for the Malay MHSAS and the scale's unidimensionality was consistent with the findings of its developers, Hammer et al (16). The present study also provided support for the scale's concurrent validity, and demonstrated high internal consistency of α=.892 [26], a value that is close to the original scale's internal consistency value (α=.92).…”
Section: Discussionsupporting
confidence: 90%
“…Participants responded using a seven‐point semantic differential scale anchored by bipolar adjectives at either end (e.g., bad vs. good ), with higher scores indicating more positive attitudes. Help‐seeking attitudes instruments that follow Azjen's () recommendations have previously demonstrated evidence of reliability (α ≥ 0.81; Hammer, Parent, & Spiker, ) and validity (e.g., significant positive association between attitudes and intention to seek help; Schomerus et al, ). Internal consistency was 0.87 (95% CI of 0.852, 0.884) in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The MHSAS is a 9item instrument that examines attitudes toward seeking help from a mental health professional if respondents hypothetically had a mental health concern (Hammer, Parent, & Spiker, 2018). Participants were asked to respond to a single statement on a 7point Likerttype scale.…”
Section: Mental Help Seeking Attitudes Scale (Mhsas)mentioning
confidence: 99%